Edukasi dan Sosialisasi Pemanfaatan Ekologi Rumah Tangga melalui Prinsip Pembangunan Berkelanjutan - Maryanti Maryanti; Elfindri Elfindri; Leli Sumarni (Warta Pengabdian Andalas, 2022)
The big challenge of sustainable development is maintaining a life-supporting environment for future generations. As the most significant energy producer, households play a significant role in reducing environmental quality. The introduction of educational activities and outreach to the Majlis 'Jannah' congregation in Sijunjung Regency aims to provide knowledge about household practices that manage and preserve the environment and apply the concept of sustainability in the household. To achieve the results of this activity, approach methods such as lectures, discussions, consultations, and comparative studies were used by visiting examples of households (Mr Abdurrahman's family) in Sijunjung Regency) that have carried out sustainable development practices. Education and socialization using an ecological philosophy with sustainable development principles such as how families manage household waste, earn additional income, reduce family expenses, and the next generation will surely enjoy what he has pioneered. The result of this activity is that the 'Jannah' congregational assembly in Sijunjung Regency has gained practical experience and knowledge regarding household ecological management so that future generations can enjoy it.